A Syrian Love Story - McAllister, Sean (United Kingdom, 2015)
Amer met Raghda in a Syrian prison cell 15 years ago. They communicated for many months through a tiny hole they secretly made in the wall. They fell in love and when released got married and started a family together. Filming began in Syria in 2009, prior to wave of changes in the Arab world – at the time, Raghda was a political prisoner and Amer was caring for their young children alone. As Raghda is released from prison, filmmaker Sean McAllister himself is arrested for filming and the political pressure around all activists intensifies. The family flees to Lebanon, and then to France. They are given political asylum in the sleepy town of Albi where they now watch the revolution from afar, waiting for Assad to fall. However, in exile, Raghda’s mental health suffers. In finding the freedom they fought so hard for, the family is beginning to fall apart.
Film also on HDD Verzio11/12 located: M22 R17 S2 R4
Verzio Film Festival Submission
Keywords: Documentary films